Analysis of Different Ways of Crosstalk Measurement in GSM Network - Musefiu Aderinola; Bokolo Abovie; Festus Okosi; Igoniderigha Daniel; G.F. Odubo (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
Crosstalk is one of the problems that affect the performance operation of global system mobile (GSM) network. Among the effect of crosstalk are call mute, call drop, wire propagation delay, dynamic power dissipation etc. Crosstalk is an undesirable signal arising due to the coupling capacitances between adjacent interconnecting wires and measured in decibel. In this paper some literature were reviewed and different ways of measuring crosstalk such as Near end croosstalk (NEXT), far end crosstalk (FEXT), Power sum crosstalk (PSNEXT) and alien crosstalk (AXT) were analyzed.